2013
DOI: 10.1002/ijch.201300072
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidative Cyclisation Reactions of 1,6‐Enynes: A Critical Comparison Between Gold and Palladium

Abstract: In transition‐metal catalysis, similar reactivities are often described for related metals, thereby resulting in the formation of similar/identical products. However, only in rare cases can similar/identical product be obtained by using non‐related metals. Amongst these reactions is the oxidative cyclisation of 1,6‐enynes by using palladium or gold. Similarities and differences will be discussed with a special focus on the diastereo‐ and enantioselective course of the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…187,188 This situation changed in 2008, when Sadighi and co-workers described the first stable, crystallographically characterized Au(I) hydride complexes of the type (IPr)AuH and [{(IPr)-Au} 2 (μ-H)] + (IPr = 1,3-bis(2,6-di-iso-propylphenyl)imidazol-2ylidene). 189 This was followed in 2012 by a report by Rosça et al of the first isolable gold(III) hydride, (C^N^C)AuH (35). 190,191 The compound was originally made from (C^N^C)AuOH and LiHBEt 3 ; later it was shown that this as well as related hydrides are more easily accessible from (C^N^C)AuCl and LiAlH 4 (Scheme 10).…”
Section: Trans-effect/trans-influencementioning
confidence: 99%
See 2 more Smart Citations
“…187,188 This situation changed in 2008, when Sadighi and co-workers described the first stable, crystallographically characterized Au(I) hydride complexes of the type (IPr)AuH and [{(IPr)-Au} 2 (μ-H)] + (IPr = 1,3-bis(2,6-di-iso-propylphenyl)imidazol-2ylidene). 189 This was followed in 2012 by a report by Rosça et al of the first isolable gold(III) hydride, (C^N^C)AuH (35). 190,191 The compound was originally made from (C^N^C)AuOH and LiHBEt 3 ; later it was shown that this as well as related hydrides are more easily accessible from (C^N^C)AuCl and LiAlH 4 (Scheme 10).…”
Section: Trans-effect/trans-influencementioning
confidence: 99%
“…Consequently, the mechanisms proposed for goldmediated reactions tend to borrow heavily from the betterknown mechanisms of platinum and palladium catalysts. 35 However, there are significant differences, not least in the redox potentials: under standard conditions the Au III /Au 0 , Au I /Au 0 , and Au III /Au I potentials (1.52, 1.83, and 1.36 V, respectively) are very much more positive than Pd II /Pd 0 (0.91 V) and Pt II /Pt 0 (1.19 V). 36 Gold is therefore much more easily reduced than palladium or platinum, to either Au(I) or the metallic state, and it is often not at all easy to determine which of these forms or oxidation states are responsible for the observed catalysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From that point, the field of gold­(I) catalysis started to gain momentum year after year and still today remains one of the most active areas of research in organometallic chemistry. , This comes as a consequence of the ability of gold­(I) complexes to activate π bonds in a very selective manner. Its potential, attributed partially to relativistic effects, is illustrated by the wide molecular complexity that can be built through the gold­(I)-catalyzed cycloisomerization of enynes (Scheme ). …”
Section: Introductionmentioning
confidence: 99%
“…Arising from complex mechanistic scenarios, the generated cyclopropyl gold carbenes can oftentimes evolve or be trapped to form isolable products containing 3- or 4-membered carbocycles. …”
Section: Introductionmentioning
confidence: 99%